PKM Olahan Pisang Dingin Gunung Maligas Melalui Digital Marketing - Ardiani, Winda; Putra, Rizki; Daulay, Arasy Ayu Setiamy (Jurnal Visi Pengabdian Kepada Masyarakat, 2024)
There are many problems and obstacles faced by micro-enterprises that often hinder business development. Starting from the lack of knowledge about business development, product standardization and mastery of current technology. And the most often happens is limited sales access due to lack of understanding marketing strategies. The problems faced by partners include that partners do not have the right marketing strategy to develop their business. Solutions include business management assistance, brand management and digital marketing. The output of this service includes increasing business development knowledge and partner skills in marketing through digital marketing.